The implementation and side effect management of immune checkpoint inhibitors in gynecologic oncology: a JAGO/NOGGO survey - Maximilian Riedel; Helene Herrmann; Thomas Bartl; Anna-Maria Rossner; Anna Tatzber; Chiara Flethe; Dario Zocholl; Barbara Schmalfeldt; Jalid Sehouli; Klaus Pietzner (BMC Cancer)
Abstract Background The integration of immune checkpoint inhibitors (ICIs) into routine gynecologic cancer treatment requires a thorough understanding of how to manage immune-related adverse events (irAEs) to ensure patient safety. However, reports on real-world clinical experience in the management of ICIs in gynecologic oncology are very limited. The aim of this survey was to provide a real-world overview of the experiences and the current state of irAE management of ICIs in Germany, Switzerland, and Austria. Methods We designed a questionnaire consisting of 34 items focused on physicans’ clinical experiences with ICIs and their management of irAEs. The survey was distributed between October 2022 and May 2023 to medical professionals with experience in the field of gynecologic oncology. Results A total of 221 gynecologists participated in the study. Most respondents (n = 130, 59.1%) were primarily engaged in gynecologic oncology at the time of the survey, with an average of ten years of clinical experience. Individual experiences with regard to irAEs varied significantly. When asked which irAEs they had observed “frequently” or “very frequently”, respondents most commonly reported thyroiditis (37.2%), followed by skin reactions (23.6%), and pneumonitis (10.6%). A total of n = 16 (7.4%) reported at least one death of a patient due to irAEs. Feeling “unconfident” or “very unconfident” about managing irAEs was reported by 35.6% (n = 78). With regard to clinical management of adverse events after discontinuation of treatment, 32.4% (n = 68) ceased to inquire about irAEs after six months. Conclusion The results of this survey provide valuable insights into physicians’ real-world experiences with irAEs associated with ICI treatment. Dealing with serious immune-related and potentially life-threatening side effects has become a routine aspect of clinical practice. Many physicians, however, express a lack of sufficient familiarity with irAEs and their management. Therefore, it is essential to improve medical education, specialized oncological training, and close interdisciplinary collaboration to improve patient care.